The impact of the IPO on the stock performance of companies in the industrial and energy sector listed on the Casablanca stock exchange - Ayoub, Massiki; Olaya, Metwalli; Salma, Dib; Omar, Kharbouch (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to assess the impact of initial public offerings (IPOs) on the stock market performance of Moroccan companies operating in the industrial and energy sectors. It seeks to understand how going public affects profitability, financial structure, and valuation, particularly in the context of an emerging market. The research is grounded in financial theories related to capital structure, corporate governance, agency theory, and signaling. It employs a quantitative approach using econometric models, Generalized Linear Models (GLM), Cross-Sectional Autoregressive Distributed Lag (CS-ARDL), and Ordinary Least Squares (OLS) to evaluate both short- and long-term stock performance. Key variables analyzed include market conditions, liquidity, and stock price volatility. The results indicate a significant improvement in stock returns following IPOs, primarily driven by favorable market conditions and high stock liquidity. However, excessive stock volatility emerges as a detrimental factor, negatively influencing future performance. The findings underscore the dual nature of IPO outcomes: while they can enhance returns in the short term under certain conditions, unmanaged volatility can hinder sustained performance. A nuanced approach is therefore essential for companies considering public listing. This study provides practical insights for industrial and energy firms in Morocco and similar emerging markets. It recommends that firms carefully evaluate market timing and implement measures to manage post-IPO volatility to optimize long-term value creation.